Triphenylamine isophorone derivatives with two photon absorption: Photo-physical property, DFT study and bio-imaging. (September 2015) - Gan, Xiaoping; Wang, Yang; Ge, Xinping; Li, Wei; Zhang, Xiuzhen; Zhu, Weiju; Zhou, Hongping; Wu, Jieying; Tian, Yupeng
Abstract: Six multi-branched compounds (1 –6 ) were conveniently synthesized through condensation reaction, and characterized by 1 H NMR, 13 C NMR, MS and single crystal X-ray diffraction. One-, two-photon absorption and emission properties were studied and theoretical calculations were applied to investigate the structure–property relationships, which showed that all the six compounds possessed good two photon absorption (2PA) properties. Their 2PA cross sections increased with the isophorone's branch number, the highest 2PA cross-section was 9398.23 GM for6 in 1, 4-dioxane. Cytotoxicity tests indicated that all these compounds had good biocompatibility for living cells, bio-imaging studies highlighted the potential application of compounds1, 2, 4 and6 in both one- and two-photon fluorescence microscopy imaging domains. Graphical abstract: We have been synthesized six multi-branched compounds and they all possessed good two photon absorption (2PA) properties, the highest 2PA cross-section was 9398.23 GM for 6 in 1, 4-dioxane. Highlights: A serious of dyes with A–π–D–π–A species was reported. The structure was determined by single crystal X-ray diffraction analysis. The structure–property relationships were investigated. The two-photon absorption cross-sections were determined by two-photon excited fluorescence. The highest two-photon absorption cross-section of these compounds was 9398.23 GM.